Correlation analysis of carotid artery intima-media thickness, serum 25(OH)D and men with erectile dysfunction - Zhang, Jun-hao; Li, Wei; Wang, Cheng-yue; Zhang, An-ni; Jia, Ben-zhong; Li, Ya-wei; Shi, Zhen-duo; Tang, Kai-fa; Han, Cong-hui (Frontiers in Endocrinology, 2022)
Our goal is to investigate the connection between serum 25(OH)D and carotid artery intima-media thickness (CIMT) in men with erectile dysfunction (ED).Serum 25(OH)D and CIMT were measured in 124 participants with erectile dysfunction and 39 healthy controls. The relationship between them and different patient-related parameters and disease-related parameters was studied. Compared with the control group and mild ED group, the level of serum 25(OH)D in moderate ED group and severe ED group decreased significantly(P<0.05). The CIMT values of moderate ED group and severe ED group were higher than those of the control group(P<0.05). The CIMT value of severe ED group was significantly higher than that of mild ED group(P<0.05). IIEF-5 score was positively correlated with serum 25(OH)D level, but negatively correlated with CIMT value(P<0.05). After adjusting for the influence of confounding factors, The CIMT values, 25(OH)D and IIEF-5 score were substantially associated(P<0.05). The serum level of 25(OH)D and IIEF-5 score were positively correlated, while the CIMT values and IIEF-5 score were negatively correlated. The level of serum 25(OH)D should be analyzed in men with ED, especially in patients with vasculogenic ED, and supplementation is recommended for those who were with vitamin D deficiency.